Huangqin Qingre Qubi Capsule inhibits RA pathology by binding FZD8 and further inhibiting the activity of Wnt/β-catenin signaling pathway. (10th February 2023) - Zhou, Wanwan; Wang, Yuting; Huang, Yurong; Liu, Jian; Cheng, Chenglong; Xue, Qiuyun; Wang, Xiao; Chang, Jun; Miao, Chenggui
Abstract: Ethnopharmacological relevance: Huangqin Qingre Qubi Capsule (HQC) is a Chinese herbal compound for the treatment of rheumatoid arthritis (RA), which is made from dry roots of Scutellaria baicalensis Georgi, dry mature seeds of Gardenia jasminoides J.Ellis, dry and mature seeds of Coix lacryma-jobi var. stenocarpa Oliv., dry mature seeds of Amygdalus persica L. and roots and rhizomes of Clematis chinensis Osbeck in the proportion of 10:9:30:5:10. HQC has a significant effect in clinical treatment of RA, which can inhibit RA inflammation, improve oxidative stress state, and effectively relieve symptoms of RA patients. Aim of the study: The anti-arthritis effect of HQC and its mechanism, especially whether it improves RA through FZD8-Wnt/β-catenin signal axis, were studied using adjuvant arthritis (AA) rats and FLS from RA patients. Materials and methods: Real time qPCR (RT-qPCR), Western blot (WB), confocal microscopy and other molecular biological methods were used to study the anti-RA effect of HQC and its mechanism. Results: The expression of FZD8 was significantly up-regulated in synovium and FLS of AA rats and RA FLS. FZD8 significantly activated the Wnt/β-catenin signaling pathway, promoted abnormal proliferation of FLS, increased the levels of inflammatory factors IL-1β, IL-6 and IL-8, and significantly increased the expression of matrix metalloproteinase 3 (MMP3) and fibronectin. HQC has significant therapeutic effect on AA rats. Molecular docking and molecular dynamics showed that HQC had a good binding ability with FZD8. We also confirmed that HQC inhibited Wnt/β-catenin signaling pathway by binding FZD8, and reduced the levels of the above inflammatory factors and pathological genes of RA. Conclusions: The expression of FZD8 is significantly increased in AA rats and FLS from RA patients. Clarify that HQC improves RA through the FZD8-Wnt/β-catenin signal axis, provide a clear therapeutic mechanism for HQC to improve RA, and also provide a basis for clinical promotion of HQC. Graphical abstract: FZD8 expression was significantly up-regulated in AA rats and RA FLS. FZD8 significantly activated Wnt/β-catenin signaling pathway, promoted FLS abnormal proliferation, increased the levels of inflammatory factors IL-1β, IL-6 and IL-8, and significantly increased the expression of MMP3 and fibronectin. HQC has obvious therapeutic effect on AA rats. Combining molecular docking and molecular dynamics studies, we confirmed that HQC inhibited Wnt/β-catenin signaling pathway and RA pathology by binding FZD8. Image 1 Highlights: The FZD8 expression was significantly up-regulated in AA rats and RA FLS. FZD8 significantly activated Wnt/β-catenin signaling pathway and promoted RA. HQC had a good binding ability with FZD8. HQC improved RA through the FZD8-Wnt/β-catenin signal axis.